2013
DOI: 10.2807/1560-7917.es2013.18.33.20555
|View full text |Cite
|
Sign up to set email alerts
|

A surge of MDR and XDR tuberculosis in France among patients born in the Former Soviet Union

Abstract: on behalf of the MDR-TB Management group of the NRC. A surge of MDR and XDR tuberculosis in France among patients born in the Former Soviet Union.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 11 publications
1
16
0
1
Order By: Relevance
“…This increase is due to the (31). Incidentally, a recent study performed in the Russian Federation reported an FQ resistance rate as high as 62% in consecutive MDR-TB cases (26).…”
Section: Discussionmentioning
confidence: 99%
“…This increase is due to the (31). Incidentally, a recent study performed in the Russian Federation reported an FQ resistance rate as high as 62% in consecutive MDR-TB cases (26).…”
Section: Discussionmentioning
confidence: 99%
“…These require further study, particularly migration which has been linked to TB in recent reports in central Asia [23,24]. Migration from countries of the former Soviet Union to several European Union countries in the last decade has been marked [25], and studies such as the current one underline the importance of continued surveillance for drug-resistance in the western Europe [12,26]. Biochemical tests and expert interviewers may be needed to elicit valid answers to questions of a sensitive nature such as problem use of alcohol and narcotic drugs, lifestyles which have been associated with drug-resistant TB elsewhere in the former Soviet Union countries [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Red=Beijing strain. 103,104,[105][106][107][108][109][110][111][112] Green=LAM9 strain. 113 Light blue=Haarlem1 strain.…”
Section: Figurementioning
confidence: 99%